Combination of Classical and Group Guidance in Shaping Resilient and Delinquency-Free Adolescents - Sabrina Zakiyah (International Journal of Psychology and Mental Health, 2025)
The purpose of this study is to provide insight into the combination of classical guidance and group counseling in shaping resilient adolescents who are free from delinquency. This research employs a descriptive method with a qualitative approach. The data collection technique used is a literature study, where various books, notes, and research reports relevant to the topic serve as the theoretical foundation. The findings indicate that classical guidance and group counseling are effective in enhancing understanding and fostering strong character development in adolescents, enabling them to avoid deviant behavior. The combination of these two services provides both knowledge and interactive experiences related to delinquency, allowing students to develop better social skills and self-control. The success of this strategy depends on the active role of school counselors, as well as support from schools, families, and the community.